2022
DOI: 10.1128/spectrum.01364-22
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Nonconjugative Virulence or Resistance Plasmids Mediated by a Self-Transferable IncN3 Plasmid from Carbapenem-Resistant Klebsiella pneumoniae

Abstract: Nowadays, the underlying mobilization mechanism and evolutionary processes of nonconjugative virulence or resistance plasmids in Klebsiella pneumoniae remain poorly understood. Our study revealed the high conjugation ability of IncN3 plasmid isolated from carbapenem-resistant K. pneumoniae and confirmed its capability to mobilize the nonconjugative virulence or resistance plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Sequence analysis indicated that pCfr_tK-N was a recombinant of pCF2075-1 and pCF2075-2 mediated by IS 6100 , and this intermolecular transposition was first reported. Similar recombination, mediated by IS 26 , IS Kpn14 , IS Kpn74 , and IS 903B , was also reported in conjugations among different resistant or virulent plasmids in recent years, which could accelerate the dissemination of resistance and virulence genes (Wang et al, 2022a , b ; Yang et al, 2022 ). The pCF2075-1 being transferred by generating recombinants might be explained by the fact that the self-transferrable plasmids usually contain four modules: origin of transfer site oriT , relaxase gene, gene encoding type IV coupling protein (T4CP), and gene cluster for bacterial type IV secretion system (T4SS).…”
Section: Discussionsupporting
confidence: 57%
“…Sequence analysis indicated that pCfr_tK-N was a recombinant of pCF2075-1 and pCF2075-2 mediated by IS 6100 , and this intermolecular transposition was first reported. Similar recombination, mediated by IS 26 , IS Kpn14 , IS Kpn74 , and IS 903B , was also reported in conjugations among different resistant or virulent plasmids in recent years, which could accelerate the dissemination of resistance and virulence genes (Wang et al, 2022a , b ; Yang et al, 2022 ). The pCF2075-1 being transferred by generating recombinants might be explained by the fact that the self-transferrable plasmids usually contain four modules: origin of transfer site oriT , relaxase gene, gene encoding type IV coupling protein (T4CP), and gene cluster for bacterial type IV secretion system (T4SS).…”
Section: Discussionsupporting
confidence: 57%
“…It is worth noting that we observed extensive fragment plasmid fusions in two non-conjugative MDR and virulence plasmids contributed by several transposases. Due to the presence of various mobile elements in both MDR and virulence plasmids, we speculate that these plasmids have a high potential to fuse with other conjugative plasmids and form conjugative MDR and virulence-encoding plasmids, facilitating transmission of virulence plasmid to different types of K. pneumoniae strains ( Xie et al., 2020 ; Wang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…19,54,63 Despite their limitation in conjugation transfer, nontransmissible IncR plasmids can serve as a reservoir by fusion with other types of resistance plasmids or directly cotransfer with the helper self-transferable IncN3 plasmid, thereby enhancing its ability to transmit to other K. pneumoniae lineage or Enterobacteriaceae species. 70,71 More importantly, recent studies reminded the public that strains with this plasmid became high virulence and multidrug resistances. 61,66,[72][73][74] In this study, the tra regions in the three sequenced plasmids were incomplete compared with that in pHN7A8 and the bla KPC-2 gene was only detected in ST11, suggesting a limited horizontal transmission of this plasmid.…”
Section: Discussionmentioning
confidence: 99%